Executive Director's Message - Harley, Catherine (Operating Room Nurses Association of Canada Journal, 2013)
Governance, one of the priorities set out in the ORNAC Strategic Plan, relates to the structure of the Board of Directors and the composition of board membership. The timing of the ORNAC Governance Initiative was optimal as it coincided with the Federal Government’s new Canada Not- for- Profit Corporations Act. To comply with this new Act, and ensure ORNAC would remain relevant and sustainable in the future, the ORNAC Board of Directors needed to review the letters patent and develop “Articles of Continuance” as well as review and revise the ORNAC By-laws. During the April 20, 2013, ORNAC Annual General Meeting the Articles of Continuance and new By-laws were voted on, by the existing ORNAC members via a Special Resolution, and the motion was passed.